The healthy indoor environment how to assess occupants' wellbeing in buildings - Bluyssen, Philomena M. (London Routledge, 2014)
"The Healthy Indoor Environment aims to help architects, building engineers and anyone concerned with the wellbeing of building occupants to better understand the effects of spending time in buildings on health and comfort. In three clear parts dedicated to mechanisms, assessment and analysis, the book looks at different indoor stressors and their effects on wellbeing in a variety of scenarios with a range of tools and methods"-- Provided by publisher.
Part 1: Mechanisms -- 1. Human model -- 2. Bodily Processes -- 3. Stress Response Mechanisms -- Part 2: Assessment -- 4. Indicators -- 5. Research Methods and Analysis -- 6. Data Collection Techniques -- Part 3: Analysis -- 7. Needs and Opportunities -- 8. Performance Indicators -- 9. Scenarios
Keywords: Buildings -- Environmental engineering; Architecture -- Human factors; Architecture -- Psychological aspects; Indoor air quality